Respuesta :

Answer:

See explanation below

Explanation:

The previous answer is wrong. To do this, we need to write the equilibrium equation for each species there, and then, write the Ksp in terms of molar solubility.

Molar solubility will be called as "x". So let's write the chemical equation for each species:

a) AB(s)

In this case, the equation would be:

AB(s) <-----> A(aq) + B(aq)

Doing an ICE chart we have:

        AB(s) <------> A + B

I:                             0    0

C:                           +x   +x

E:                            x     x

In this case Ksp would be:

Ksp = [A] [B]

However, A and B are X so:

Ksp = x * x

Ksp = x²

This is the Ksp in terms of molar solubility for AB(s)

b) AB2(s)

In this case, we have two atoms of B so equation would be like this:

AB2(s) <-------> A(aq) + 2B(aq)

ICE chart:

          AB2(s) <-------> A(aq) + 2B(aq)

I:                                   0           0

C:                                 +x         +2x

E:                                  x           2x

Therefore Ksp:

Ksp = [A] [B]² ---> replacing with x:

Ksp = x * (2x)²

Ksp = x * 4x²

Ksp = 4x³

c) AB3(s)

We do the same as we did in part b, but changing concentration of B:

        AB3(s) <-------> A(aq) + 3B(aq)

I:                                   0           0

C:                                 +x         +3x

E:                                  x           3x

Therefore Ksp:

Ksp = [A] [B]³ ---> replacing with x:

Ksp = x * (3x)³

Ksp = x * 27x³

Ksp = 27x⁴

d) A3B2

We do the same, but changing concentration of A and B:

        A3B2(s) <-------> 3A(aq) + 2B(aq)

I:                                   0           0

C:                                +3x         +2x

E:                                  3x           2x

Therefore Ksp:

Ksp = [A]³ [B]² ---> replacing with x:

Ksp = (3x)³ * (2x)²

Ksp = 27x³ * 4x²

Ksp = 108x⁵

And that's all the ways of expressing the Ksp

The solubility product is the equilibrium constant for the dissolution in a substance.

We know that the molar solubility of the salt x

For the salt AB(s) ⇄ A^+(aq) + B^-(aq)

[ A^+] = [B^-] = x

Ksp = [ A^+] [B^-] = x^2

For the salt AB2(s) ⇄ A^+(aq) + 2B^-(aq)

Ksp =  [ A^+] [2B^-]^2 =  [ x] [2x]^2 =4x^3

For the salt AB3(s) ⇄ A^+(aq) + 3B^-(aq)

Ksp =  [ A^+] [3B^-]^3 =  [ x] [3x]^3 = 27x^4

For the salt A3B2(s) ⇄ A^+(aq) + 3B^-(aq)

Ksp =  [ 3A^+] [2B^-]^3 =  [ 3x]^3 [2x]^2 = 108x^5

Learn more: https://brainly.com/question/8155254

ACCESS MORE